2019
DOI: 10.1186/s12871-019-0839-y
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of disinfection effect between benzalkonium chloride and povidone iodine in nasotracheal intubation: a randomized trial

Abstract: Background Nasotracheal intubation can potentially result in microbial contamination from the upper respiratory tract to the lower respiratory tracts. However, an ideal nasotracheal disinfection method is yet to be determined. Therefore, we compared the disinfection effects between benzalkonium chloride and povidone iodine in nasotracheal intubation. Methods Overall, this study enrolled 53 patients aged 20–70 years who were classified into classes 1 and 2 as per America… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
9
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1
1

Relationship

3
5

Authors

Journals

citations
Cited by 12 publications
(10 citation statements)
references
References 17 publications
1
9
0
Order By: Relevance
“…Thus, benzalkonium chloride is considered to have an antiseptic effect that is more prolonged than that of PI. 10) Octenidine dihydrochloride 0.1% has the strongest antimicrobial activity against Staphylococcus aureus biofilms grown on vascular grafts; its antiseptic effect is superior to that of chlorhexidine combined with either PI or octenidine dihydrochloride. 11) Furthermore, preoperative hand washing is important in the prevention of surgical site infection.…”
Section: Discussionmentioning
confidence: 96%
“…Thus, benzalkonium chloride is considered to have an antiseptic effect that is more prolonged than that of PI. 10) Octenidine dihydrochloride 0.1% has the strongest antimicrobial activity against Staphylococcus aureus biofilms grown on vascular grafts; its antiseptic effect is superior to that of chlorhexidine combined with either PI or octenidine dihydrochloride. 11) Furthermore, preoperative hand washing is important in the prevention of surgical site infection.…”
Section: Discussionmentioning
confidence: 96%
“…Finally, as this study evaluated in vitro data only it is not possible to draw conclusions regarding clinical efficacy. Published trials and simulation studies have, however, demonstrated that PVP-I results in >99% reduction in bacterial or viral load after 30 seconds contact time in a number of settings (e.g., prevention of surgical site infections, antisepsis before nasotracheal intubation, mouth antisepsis for prevention of respiratory infections) [ 41 ], [ 66 ], [ 67 ], [ 68 ]. Therefore, the in vitro data presented in this study provides further support for the efficacy of PVP-I against a wide range of clinically relevant pathogens.…”
Section: Discussionmentioning
confidence: 99%
“…Until the effects of the neuromuscular blocking agent became apparent, mask ventilation was applied in all patients using 100% oxygen with propofol and remifentanil. While mask ventilation was being performed, the patients’ nasal mucosa and inferior nasal passages were adequately disinfected with benzalkonium [ 10 ] spray (ZALKONIN® SOLUTION 0.025, Kenei Phamaceutical Co., Ltd., Osaka). During disinfection, swabbing was not done to avoid nasal bleeding.…”
Section: Methodsmentioning
confidence: 99%
“…Although this method is very useful in operations wherein the operative field and airway are congruent, some complications associated with NTI include nasal bleeding [ 1 , 2 ], bacteremia [ 3 ], retropharyngeal perforation [ 4 ], and partial or complete obstruction of the tube [ 5 , 6 ] has been reported. Several effective preventive measures against nasal bleeding, retropharyngeal perforation, and bacteremia have been reported [ 7 10 ]. Previous studies [ 11 13 ] have compared vasoconstriction effect of epinephrine (E) and xylometazoline during NTI; however, xylometazoline is not available in authors’ country.…”
Section: Introductionmentioning
confidence: 99%